Pengaruh Pengaruh Massage Effleurage terhadap Penurunan Intensitas Nyeri Persalinan Kala 1 - HESTI EKA PRIHATININGRUM; Kamidah; Anna Uswatun Qoyyimah (Universitas Muhammadiyah Klaten, 2026)
Background: Labor pain is a physiological process, but if not managed properly it can increase stress and tension, which triggers an increase in adrenaline hormones and decreases blood flow to the uterus, thereby increasing the intensity of pain. One non-pharmacological method to reduce pain is effleurage massage. This technique works by stimulating large nerve fibers and activating the release of endorphins, which can inhibit pain signals to the brain through the gate control theory mechanism. Objective: To determine the effect of effleurage massage on reducing the intensity of labor pain in the first stage at PKU Muhammadiyah Karanganyar Hospital. Method: Using a pre-experimental design with a one group pretest-posttest approach. The sample consisted of 30 mothers in the first stage of labor who were selected using the consecutive sampling method. Data analysis used the Wilcoxon test. Results: The study showed that out of 30 respondents before being given effleurage massage, the majority of respondents experienced moderate pain as many as 21 respondents (70%) and after being given effleurage massage, the majority of respondents experienced mild pain as many as 20 respondents (67%), moderate pain 10 respondents (33%) and none experienced severe pain (0%). Statistical tests showed an Asymp. Sig. (2-tailed) value of 0.000 (<0.05), which means there is a significant difference. Conclusion: Effleurage massage has an effect on reducing the intensity of pain in the first stage of labor.